Defying the odds : banking for the poor - Versluysen, Eugene (West Hartford, Conn. : Kumarian Press, 1999)
The book draws from the experience of selected creative microfinance programs in Asia, West Africa, and Latin America. The book focuses on the context of social and economic change in developing countries, claiming the poor do not create poverty. The book s focus on grassroots developmental entrepreneurship and alternative poverty-reduction strategies will be of interest to policymakers as well as students who are learning how microfinance has grown worldwide.
Includes index.
Includes bibliographical references (p. 239-242).
lje 12/07/2016, ijb 07/03/2019
Loans
Keywords: Banks and banking; Credit; Small business; Poor; Economic development